The concept of care throughout history - Raquel Alba Martin (Cultura de los Cuidados, 2015)
Introduction: Etymologically care concept comes from the term “’ll take care / curare.” The word care has different meanings in our language. The most immediate and popular works as a warning of impending danger; This is one of the words a child learns first and now, for the elderly, we use it as profusion throughout life.